2013
DOI: 10.1007/s13312-013-0109-x
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine induced skin rash

Abstract: Gemcitabine is used in various carcinomas like lung cancer, pancreatic cancer, bladder cancer and breast cancer in adults. It is considered to be a well-tolerated drug with little known side effects [1]. The reported toxic effects of gemcitabine include myelosuppression, altered liver function tests, flu-like syndrome, bronchospasm, rash, itching, and fever [2]. Skin reactions are rarely reported [1-4], the reported incidence being 7%-30% [4].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…[26][27][28] Of significance, multiple studies have reported the abilities of PAFR antagonists to control the growth of cancer cells or augment the responses of therapeutic agents. 26,29,30 Given that gemcitabine chemotherapy used against multiple human malignancies either alone or in combination with other agents, exhibits adverse effects, including skin rash/necrosis, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] our current studies sought to determine the potential role of MVP release in the pathologic effects of topical gemcitabine application. To that end, pharmacologic approaches using human skin explants and genetic approaches using murine skin were used as relevant models.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[26][27][28] Of significance, multiple studies have reported the abilities of PAFR antagonists to control the growth of cancer cells or augment the responses of therapeutic agents. 26,29,30 Given that gemcitabine chemotherapy used against multiple human malignancies either alone or in combination with other agents, exhibits adverse effects, including skin rash/necrosis, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] our current studies sought to determine the potential role of MVP release in the pathologic effects of topical gemcitabine application. To that end, pharmacologic approaches using human skin explants and genetic approaches using murine skin were used as relevant models.…”
Section: Discussionmentioning
confidence: 99%
“…MVPs were resuspended in filtered PBS and the concentration was determined via nanosight tracking analysis (NTA) using the NanoSight NS300 instrument (NanoSight Ltd, Malvern Instruments, Malvern, UK) as per our published reports 29–31 . The baseline MVP release from human and murine skin by vehicle (control) treatment ranges from 10 8 to 10 9 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations